Doing with understanding: Lessons from research on problem- and project-based learning - Barron, Brigid; Schwartz, Daniel L.; Vye, Nancy J.; Moore, Allison; Petrosino, Anthony; Zech, Linda; Bransford, John D. (The journal of the learning sciences, 1998)
A major hurdle in implementing project-based curricula is that they require simultaneous changes in curriculum, instruction, and assessment practices-changes that are often foreign to the students as well as the teachers. In this article, we share an approach to designing, implementing, and evaluating problem- and project-based curricula that has emerged from a long-term collaboration with teachers. Collectively, we have identified 4 design principles that appear to be especially important: (a) defining learning-appropriate goals that lead to deep understanding; (b) providing scaffolds such as
Keywords: apprentissage par projet; contexte d'apprentissage; enseignement primaire; résolution de problème; sciences